Political Disengagement Among Youth: A Comparison Between 2011 and 2020 - Zhang, Weiyu (Frontiers in Psychology, 2022)
This study answers one general question using a country case: what shapes the young generations’ political disengagement in Singapore? Taking the generational differences and institutional influence perspectives, this study highlights the time dimension to show the ebb and flow of political and (new) media landscape changes in a non-Western context, Singapore. By comparing focus group discussions conducted among 19-30 years old in 2011 vs. 2020, this paper finds that despite of similarly claiming disinterest in politics, the 2011 youth were more attentive to political news than the 2020 youth. The changes in political institutions gave rise to this increased situational engagement. However, the gap between paying attention and taking action was still large in 2020, or even larger than in 2011, due to the increased complexity and competitiveness of politics that the 2011 youth observed via social media. The persistence of political disinterest suggests its dispositional connections to psychological barriers that are socially constructed over generations.